Optimization of flow division pier distribution for a sedimentation tank in the Oujiang Water Diversion Project - Chen, Jian; Zhang, Liyan; Wu, Xianghua; Tian, Xiaoping; Zheng, Jingyun; Zhao, Renhuai; Qiu, Hao (Frontiers in Earth Science, 2025)
Sedimentation tank design is of key importance in a water diversion project. Both physical and numerical models are used to study the hydrodynamics and sediment transport in the sedimentation tank of the Oujiang Water Diversion Project. The water inlet central axis is inclined sharply against the sedimentation tank central axis. The physical model adheres to the principle of gravitational similarity, with a geometric scale of 1:20. Four rows of division piers are designed and optimized to effectively separate the flow, ensure efficient sedimentation, and prevent sediment re-suspension. The numerical model simulates the graded sediments. The simulations are carried out under designed low, standard, and high water levels. The numerical results are in good agreement with the experimental measurements. The main flow is focused on the left bank of the tank due to the large angle between the inlet gate and the tank axis. Consequently, a large-scale backflow region forms on the right bank. After optimizing the flow division piers at the tank inlet, the main flow velocity significantly decreases, becoming smoother and more uniform, with no reversal flow areas. As a result, the sediment concentration distribution becomes more uniform, and the sedimentation rate increases notably.